IbI logics optimization algorithm-based high-order sliding mode control for DSIG within a wind turbine system - Khaled Benzaoui; Abderrahmen Bouguerra; Samir Zeghlache; Ahmed Elsanabary; Saad Mekhilef; Ahmed Bendib; Houssam eddine Ghadbane; Hegazy Rezk (Results in Engineering)
Applying advanced control strategies with optimal parameters tuning is challenging for ensuring good tracking performance and stable operation of the dual-stator induction generator-based wind turbine (WT-DSIG) systems. To this end, the present paper proposes an innovative tuning method using an incomprehensible but intelligent-in-time logic algorithm (ILA) to ensure optimal HOSMC controller parameters tuning. The optimally tuned HOSMC controller-based FOC scheme is applied to control a WT-DSIG system. This research offers a simple and effective method for optimal tuning of the control parameters, improving the control performance, hence the WT-DSIG system's stability. The proposed method is superior to the existing techniques, as it uses the IbI, a metaheuristic stochastic algorithm, to optimize the gains of the flux, speed, and current HOSMC controllers simultaneously. The effectiveness of the proposed control approach is assessed based on a hardware-in-the-loop (HIL) implementation in a PLECS/RT Box real-time simulator. The HIL findings through comparative study further confirm the superiority of the optimally designed controllers over the conventional ones, highlighting significant enhancements in dynamic, steady-state, THD, and some other metrics. This research has practical implications for designing and operating WT-DSIG systems, offering a promising solution for improving their stability and performance.